The Popular Theatre Movement in Russia 1862-1919. - Thurston, Gary (Studies in Russian literature and theory., 1998)
After the emancipation of the serfs in 1861, educated Russians began to present plays as part of a crusade to "civilize" the peasants. Relying on archival and published material virtually unknown outside Russia, this study looks at how playwrights criticized Russian social and political realities, how various groups perceived their plays, and how the plays motivated viewers to change themselves or change their circumstances. The picture that emerges is of a potent civic art influential in a way that eluded and challenged authoritarian control.